Policy Strategy in Optimizing the Economy of Salt Farming Communities in North Sumatera and Aceh - Fauzi Arif Lubis; Muhammad Arif (International Journal of Artificial Intelligence Research, 2022)
Many Indonesian people live in coastal areas in a country with a vast sea. However, unfortunately, the vastness of this sea does not cause Indonesia to become a salt exporting country. North Sumatra can still not produce salt optimally as an area with an enormous enough salt-producing potential. This study aims to analyze the policy strategies that need to be carried out to optimize the economy of salt farming communities in North Sumatra and Aceh. This research will use a qualitative approach. The data used in this study came from various interviews and literature studies. This study found a potential for salt production in North Sumatra and Aceh. However, unfortunately, this potential still cannot be optimized due to various factors. The government then provided training and assistance for salt farmers in North Sumatra and Aceh to increase the optimization of salt production in the two provinces.